The D2 antagonist sulpiride modulates the neural processing of both rewarding and aversive stimuli in healthy volunteers - McCabe, C; Huber, A; Harmer, C; Cowen, P (2011)
Rationale Animal studies indicate that dopamine pathways in the ventral striatum code for the motivational salience of both rewarding and aversive stimuli, but evidence for this mechanism in humans is less established. We have developed a functional magnetic resonance imaging (fMRI) model which permits examination of the neural processing of both rewarding and aversive stimuli. Objectives The aim of the study was to determine the effect of the dopamine receptor antagonist, sulpiride, on the neural processing of rewarding and aversive stimuli in healthy volunteers. Methods We studied 30 healthy participants who were randomly allocated to receive a single dose of sulpiride (400 mg) or placebo, in a double-blind, parallel-group design. We used fMRI to measure the neural response to rewarding (taste or sight of chocolate) and aversive stimuli (sight of mouldy strawberries or unpleasant strawberry taste) 4 h after drug treatment. Results Relative to placebo, sulpiride reduced blood oxygenation level-dependent responses to chocolate stimuli in the striatum (ventral striatum) and anterior cingulate cortex. Sulpiride also reduced lateral orbitofrontal cortex and insula activations to the taste and sight of the aversive condition. Conclusions These results suggest that acute dopamine receptor blockade modulates mesolimbic and mesocortical neural activations in response to both rewarding and aversive stimuli in healthy volunteers. This effect may be relevant to the effects of dopamine receptor antagonists in the treatment of psychosis and may also have implications for the possible antidepressant properties of sulpiride. © 2011 Springer-Verlag.